Information coordination of biological and technical objects in the vegetation chamber. (December 2019) - Klyuchka, Yevgeniya; Lukyanov, Alexander; Donskoy, Danila; Katin, Oleg; Vernezi, Miroslav; Goryanina, Ksenia; Drynkin, Yevgeniy; Tregubenko, Lyubov'
Abstract: The central problem of the use of LEDs in greenhouse production is the establishment of a causal relationship between the environment in a parametric microclimate and the manifested properties of a biological object (phenological, biological, spectral sensitivity). Information management systems with biofeedback relate to biotechnical systems in which a biological object directly participates in the formation of control decisions in real time. At the same time, the plant as a biological object detects a feedback channel from the source, which indicates the external plant characteristics (phenomenological and spectral characteristics, intensity of such processes as photosynthesis, respiration, transpiration, etc.).